2010
DOI: 10.1021/es9036786
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyl and Low Polybrominated Diphenyl Ether Transfer to Milk in Lactating Goats Chronically Exposed to Contaminated Soil

Abstract: This study investigated milk excretion kinetics of PCBs, tetra-BDE (BDE 47), and penta-BDE (BDE 99) in goats exposed to contaminated soil under controlled conditions. The animals were fed (80 days) with feed containing 5% of contaminated soil. During this exposure period, milk was analyzed weekly. At the end of the experiment the PCBs and PBDEs retained in hepatic and adipose tissues were also determined. The soil-milk carry over rates (CORs) of PCBs ranged from 6 to 62%. This result suggests that a large part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Ounnas et al. () studied the transfer of PCBs from contaminated soil in three lactating goats and observed that steady‐state conditions in milk were obtained after two weeks (total duration 76 days). TRs were estimated at day 45 for part of the PCBs, being 6% and 47% for PCB‐77 and ‐126, and 57%, 59%, 21%, 62%, 52% and 48% for the mono‐ ortho PCB‐105, ‐118, ‐123, ‐156, ‐157 and ‐167.…”
Section: Assessmentmentioning
confidence: 99%
“…Ounnas et al. () studied the transfer of PCBs from contaminated soil in three lactating goats and observed that steady‐state conditions in milk were obtained after two weeks (total duration 76 days). TRs were estimated at day 45 for part of the PCBs, being 6% and 47% for PCB‐77 and ‐126, and 57%, 59%, 21%, 62%, 52% and 48% for the mono‐ ortho PCB‐105, ‐118, ‐123, ‐156, ‐157 and ‐167.…”
Section: Assessmentmentioning
confidence: 99%
“…While PCB and PBDE concentrations in sera of beef cattle were lower than in dairy cattle, the reported concentrations are still able to make into dietary samples prepared for human consumption. This is illustrated by a study surveying meat samples at a U.S. market detecting PCBs and PBDEs in meat products derived from beef cattle (Huwe and Larsen, 2005) and multiple studies in Europe detecting PCBs and PBDEs in the animal tissues of cattle and goats (Kierkegaard et al, 2007; Ounnas et al, 2010). Unfortunately these past studies mainly looked at dioxin-like POPs, so it is difficult to make comparisons to this study, which focused mainly on the NDL congeners.…”
Section: Resultsmentioning
confidence: 99%
“…10 Optimization of an in vitro method to measure the bioaccessibility of polybrominated diphenyl ethers······ 1743 obtained using other methods. However, while the in vivo bioavailability data of PBDEs in dust/soil and other matrices were relatively plentiful (Örn and Klasson-Wehler, 1998;Hakk et al, 2002;Huwe et al, 2008;Kierkegaard et al, 2009;Ounnas et al, 2010), very limited data of the PBDE bioaccessibility in dust have been reported (Lepom et al, 2010). Thus, besides comparing with the bioaccessibility data in dust in the literature, we also compared our data to the in vivo bioavailability of PBDEs in dust/soil and other matrices.…”
Section: Comparison Of Bioaccessibility With In Vivo Bioavailabilitymentioning
confidence: 99%
“…Huwe et al (2008) investigated the bioavailability of PBDEs in dust by dosing rats with the NIST SRM 2585 dust in rat chow (containing 4% fat) and reported a broad range of bioavailability of PBDEs (from 18.9% to 78.4%) with an average of 52.3% for tri-to hepta-BDE congeners. Another study reported the bioavailability of spiked BDE47 and BDE99 in soil (aged at 21°C for 40 days) on goat at more than 30% (Ounnas et al, 2010). In addition, the bioavailability of tri-to hexa-BDE congeners in other matrices on animals was reported to vary between 47% and 86% (Örn and Klasson-Wehler, 1998;Hakk et al, 2002;Kierkegaard et al, 2009).…”
Section: Comparison Of Bioaccessibility With In Vivo Bioavailabilitymentioning
confidence: 99%